2015
DOI: 10.1108/jpmh-04-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Students ' understandings of mental health and their preferred learning platforms

Abstract: Purpose – The purpose of this paper is to examine students’ understandings of mental health and their learning preferences, in order to provide guidance for developing targeted mental health education. Design/methodology/approach – A study-specific self-administered questionnaire was used at two English schools (n=980; ages 11-18), incorporating a combination of open-ended and fixed-choice items. Data were subject to content analysis, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Engaging them in the dialogue may be more useful. Bone, Dugard, Vostanis, and Dogra (2015) found that young people were aware that there is information that may be incorrect on the Internet so needed to be treated carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging them in the dialogue may be more useful. Bone, Dugard, Vostanis, and Dogra (2015) found that young people were aware that there is information that may be incorrect on the Internet so needed to be treated carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Using social media as a learning platform needs further evaluation for a better understanding of adolescents' preferences (Bone et al, 2015) and how they engage with information online (Fergie et al, 2016). This is especially important as research into adolescent social media use "is still in its infancy" (Allen et al, 2014, p.21).…”
Section: Promotion and Prevention Are Important To Address This Problmentioning
confidence: 99%
“…Orang muda sadar bahwa ada informasi yang mungkin salah di Internet sehingga perlu diperlakukan dengan hati-hati. 37 Teknologi telah mengubah kehidupan remaja dan telah mengubah wajah interaksi sosial, namun biaya ini masih relatif tidak diketahui. 38 Saat ini, remaja bukan ahli menavigasi dunia virtual tetapi keterlibatan terus menerus dengan media sosial dapat meningkatkan ini.…”
Section: Diskusiunclassified